Sosialisasi Dampak Negatif Perkawinan Usia Muda Bagi Remaja Muda Kelurahan Tamalate Berbasis Islami - Putra, Abdur Rahman Adi Saputera (Madani: Jurnal Pengabdian Ilmiah, 2024)
Abstract: This activity aims to provide teenagers with a better understanding of Islam's view of young marriage and its positive and negative impacts. This activity was held at the Sabililhuda Mosque in Bokiowutango on September 10, 2023 and was attended by 57 young teenagers from Tamalate Village. The results of this activity showed that participants experienced a significant increase in understanding of Islamic views on marriage, requirements in religion, as well as the negative impact of young marriage. Their awareness of the health risks, educational barriers, and social aspects associated with the practice of young marriage also increased. This activity also led to a change in positive attitudes towards young marriage among participants. They begin to consider more seriously the impact of marriage in their lives and reflect on religious values in marriage decision-making. With a deeper understanding and accurate information, it is hoped that this activity will help adolescents in Tamalate Village make wise marriage decisions and in accordance with religious values in the context of marriage.